Assessment of Programmed Cell Death of Aspergillus flavus by Triggered Cysteine-dependent Aspartate-directed Proteases (Meta-caspase3) Lethality Mechanism of Novel Compounds Isolated from Ethyl Acetate Extract of Spondias mombin - Osuntokun, Oludare Temitope; Omotuyi, Olaposi I; Oluduro, Anthonia O; Idowu, Thomas O (Biochemistry and Modern Applications, 2020)
Biochemistry and Modern Applications, Vol. 2, No 1, p.30-34.